A call to incorporate a reproductive justice agenda into reproductive health clinical practice and policy - Gilliam, Melissa L.; Neustadt, Amy; Gordon, Rivka (Contraception, 2009)
Keywords: approches et analyses; contraception; discipline; droits des femmes*; intersectionnalité; inégalités; justice reproductive; justice sociale; médecine; ressource en ligne; santé; santé des femmes*; sciences; sciences humaines; sexologie; systèmes d'oppressions; thématiques

The Cyborg Embryo: Our Path to Transbiology - Franklin, S. (THEORY CULTURE AND SOCIETY, 2006)
It is useful on the occasion of the 21st anniversary of the ‘Cyborg Manifesto’ not only to reconsider its lessons in the context of what is frequently described as the re-engineering of ‘life itself’, but to look at Haraway’s earlier work on embryos. In this article I begin with Haraway’s analysis of embryology in the 1970s to suggest her cyborg embryo was already there, and has, if anything, gained relevance in today’s embryo-strewn society. I argue further, as the title suggests, that the cyborg embryo has been crucial in defining our path to what I am calling here, building on Haraway’s notion of trans from Modest_Witness, ‘transbiology’ - broadly meaning stem cell research, cloning, tissue engineering and regenerative medicine. To illustrate this argument I draw on recent ethnographic fieldwork in a new stem cell derivation facility in the UK built adjacent to an IVF surgery. Using this example, I explore the important and paradoxical role of IVF in the emergence of stem cell science, cloning and transbiology, suggesting that Haraway’s analysis remains crucial to understanding the ironic and contradictory, and unexpectedly generative, circumstances through which the IVF-stem cell interface - the door to transbiology - came into being.
Keywords: approches et analyses; biologie; care; corps; cours; discipline; discours dominant; fecondation in vitro; féminisme cyborg; justice reproductive; lit4700; maternité; premier cycle; ressource en ligne; santé; sciences; sciences humaines; sociologie; systèmes d'oppressions; thématiques